Relationship Between Complementary Foods and Family Income on Stunting in Toddlers - Evi Hudriyah Hukom; Wahyuni Maria Prasetyo Hutomo; Resa Juli Prakoso (PT.Mantaya Idea Batara, 2023)
Stunting is a condition of failure to thrive that occurs in toddlers, one of the causes of which is chronic malnutrition. This condition can be seen from the height of the child who is shorter than children in the same age. The incidence of stunting in the world reaches 149 million toddler and based on the survey of Indonesia Nutrition Status (SSGI) 2021 in Indonesia in 2019 it reached 27.7%, in West Papua in 2019 it was 24.6% and in Sorong it reached 1026 toddler. The purpose of this study was to determine the relationship between complementary feeding and family income to the incidence of stunting in the working area of ??the East Sorong Public Health Center, Sorong City. This study used a cross sectional approach. The sample of this study were 77 toddlers aged 24-60 months with sampling using purposive sampling technique. Data analysis using Chi-Square test. The results showed that the history of complementary feeding had a relationship with the incidence of stunting (p-value = 0.017) but family income did not have a relationship with the incidence of stunting (p-value = 0.802).